Respectful and disrespectful care in the Czech Republic: an online survey - Cecily Begley; Natalie Sedlicka; Deirdre Daly (BMC, 2018)
Abstract Background Respectful maternity care includes treating women with dignity, consulting them about preferences, gaining consent for treatment, respecting their wishes, and giving care based on evidence, not routines. In the absence of any documented evidence, this study aimed to ascertain maternity care-givers' perceptions of respectful care provided for childbearing women in Czech Republic. Methods Following ethical approval, an online quantitative survey with qualitative comments was completed by 52 respondents recruited from workshops on promoting normal birth, followed by snowball sampling. The majority were midwives (50%) or doulas (46%) working in one of 51 hospitals, or with homebirths. Chi-square analysis was used for comparisons. Results Non-evidenced-based interventions, described as 'always' or 'frequently' used in hospitals, included application of electronic fetal monitoring in normal labour (n = 40, 91%), shaving the perineum (n = 10, 29%), and closed-glottal pushing (n = 32, 94%). Positions stated as most often used for spontaneous vaginal births were semi-recumbent (n = 31, 65%) or lying flat (n = 15, 31%) in hospital, and upright at home (n = 27, 100%). Average episiotomy and induction of labour rates were estimated at 40 and 26%, respectively, higher than accepted norms. Eighteen respondents (46%) said reasons for performing vaginal examinations were not explained to women in hospitals, and 21 (51%) said consent was 'never' sought. At home, 25 (89%) said reasons were explained, and permission 'always' sought (n = 22, 81%). Thirteen (32%) said hospital clinicians explained why artificial rupture of membranes was necessary, but only ten (25%) said they 'always' sought permission. The majority said that hospital clinicians 'never'/'almost never' explained reasons for performing an episiotomy (13 = 34%), gained permission (n = 20, 54%) or gave local anaesthetic (n = 19, 51%). Contrastingly, 17 (100%) said midwives at home explained the reasons for episiotomy and asked permission. When clinicians disagreed with women's decisions, 13 (35%) respondents said women might be told to 'face the consequences', six (16%) stated that the 'psychological pressure' experienced caused women to 'give up and give their permission', and four (11%) said the intervention would be performed 'against her will.' Conclusions Findings reveal considerable levels of disrespectful, non-evidenced-based, non-consensual and abusive practices that may leave women with life-long trauma.